Surgical treatment of vaginal vault prolapse - Withagen, MIJ; van der Weiden, RMF; Vierhout, ME (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Vaginal vault prolapse can cause limitations in physical and social functioning. This problem will enhance with the increasing age in women. New surgical techniques, like tension free vaginal mesh and laparoscopic sacrocolpopexy reduce surgical strain in patients and make prolapse surgery achievable in elderly women. doi:10.3126/njog.v2i2.1446 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 3 - 8